Application of Cyber Notary as a Solution in Making Electronic GMS Minutes During Pandemic Situation - Windarrahman, Hanif (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Abstract: This article analyses the application of cyber notary in making the Deed of Minutes of the Electronic General Meeting of Shareholders (GMS). The purpose of this article was to find out the juridical analysis regarding the application of cyber notary in the making of the minutes of the electronic GMS. The result of this research is the GMS electronically divided into two types of companies, Public Companies and Closed Companies. A Public Company in making the minutes of the meeting has a legal base in the Financial Services Authority Regulation Number 16/POJK.04/2020 concerning the Electronic Implementation of the General Meeting of Shareholders of a Public Company, while for a Closed Company it has a legal base in Article 77 of Law Number 40 of 2007 concerning Limited Liability Companies. In making the Deed of Minutes of the Electronic GMS held by a Public Company, the Notary can make a deed of the minutes of the GMS by cyber notary. As for closed companies, it’s divided into two reasons for making the deed: firstly, a meeting discussing changes to the articles of association can be made a Deed of Statement of Meeting Resolutions, secondly, the meeting that discusses other than changes to the articles of association can be made a Deed of Minutes of the GMS by cyber notary. Keywords: Notarial Deed; Cyber Notary; Limited Liability Company; Electronic General Meeting of Shareholders.